Physical activity profile of the professors of padjadjaran university based on global physical activity questionnaire - Maulida, Mutia Nur; Lubis, Leonardo; Sari, Dian Marta (Folia Medica Indonesiana, 2017)
Physical activity is one of the factors which determines one's health and fitness, including the professors of Padjadjaran University, as it might support their academic performances. Global Physical Activity Questionnaire (GPAQ) may describe physical activity. The purpose of this study was to describe physical activity profile of the professors of Padjadjaran University based on GPAQ. Physical activity profile which was classified as gender, age group, recommendation fulfillment, and intensity variables by present-ing quantity (n) and percentage (%) was obtained from 141 professors who fulfilled the inclusion criteria. The result of this des-criptive-quantitative study showed that 109 of the respondents were male, and 32 were female. According to WHO age group cate-gories, 35 respondents were middle aged, 78 were elderly, and 28 were late elderly. Fifty-eight respondents (41.1%) did not fulfill minimal recommendation for physical activity, 114 respondents (80.8%) underwent moderate activity and 29 respondents (20.6%) underwent vigorous activity. Therefore, it can be concluded that professors of Padjadjaran University, which were mostly middle-aged men, did not fulfill minimal recommendation for physical activities, although many of them underwent moderate activities in their daily routines.